2020
DOI: 10.15294/kemas.v16i1.11324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Katuk (Sauropus androgunus (L) Merr) Leaf Biscuit on Increasing Prolactine Levels of Breastfeeding Mother

Abstract: Prolactin is one of the important hormones for increasing the synthesis and secretion of breast milk. Katuk (Sauropus androgunus (L) Merr) leaf biscuits are standardized and practical processed food products that are substituted with katuk leaf extract and have met the requirements as additional food for breastfeeding mothers. In addition to nutritional content, katuk leaf biscuits also contain phytochemical compounds, namely steroids and alkaloids. The purpose of this study was to determine the effect of katu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…15 Recent study by Indryani et al also shows that katuk leaves supplementation in biscuit form also significantly increases prolactin level. 14 These several findings proved that katuk leaf provided a beneficial effect on milk production and increase prolactin level.…”
Section: Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…15 Recent study by Indryani et al also shows that katuk leaves supplementation in biscuit form also significantly increases prolactin level. 14 These several findings proved that katuk leaf provided a beneficial effect on milk production and increase prolactin level.…”
Section: Reviewmentioning
confidence: 85%
“…Thus, to maintain breast milk production, it is necessary to have high levels of Prolactin. 14 It is proven that in the case of mothers with premature babies with gestational age ≤ 36 weeks, there is no milk production, and it turns out that the basal prolactin hormone level is 45 ng/ml. Whereas for mothers who deliver term babies and can express breast milk, it turns out that the hormone prolactin level reaches 90-110 ng/ml.…”
Section: Reviewmentioning
confidence: 99%
“…Moringa contains phytosterols, which act as a galactagogue, stimulating breast milk secretion [36][37][38]. Similarly, katuk leaves can boost breast milk production [28,39]. Breast milk secretion has also been reported to be stimulated by banana flowers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the treatment, several food ingredients are expected to give a lactogenic effect including Sauropus androgynous or known locally as "katuk leaves" and papaya leaves. Sauropus androgynous is a potential commodity easily found in Indonesia, so far many Indonesian people had experienced the benefits, but the scientific evidence to measure its effect on breastmilk volume are still scarce (Indrayani et al 2020;Santoso 2016;Suwanti & Kuswanti 2015;Pinem et al 2019). Supplements containing these ingredients have been consumed among Indonesian mothers to increase breast milk production (Suwanti & Kuswati 2015).…”
Section: Ngadiarti Et Almentioning
confidence: 99%
“…Papaya leaves juice stimulates prolactin hormone level, while mung beans, besides having galactagogue effect, also contains thiamine or vitamin B1 which converts carbohydrates into energy and reduces stress, as well as triggers oxytocin secretion (Wulandari & Jannah 2015;Ikhlasiah et al 2020). Previous studies reported that these effects were due to a dilate blood vessels on the mammary glands and secretory cell proliferation that increase blood flow (Indrayani et al 2020;Foong et al 2020). These are related to phytochemical groups' effect on galactopoietic (Mohanty et al 2014).…”
Section: Breastmilk Volume Breastfeeding Frequency and Durationmentioning
confidence: 99%